2016
DOI: 10.1188/16.onf.e161-e169
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue, Burnout, and Compassion Satisfaction Among Oncology Nurses in the United States and Canada

Abstract: Purpose: This study explored the role of several psychological factors in professional quality of life in nurses. Specifically, we tried to clarify the relationships between several dimensions of empathy, self-compassion, and psychological inflexibility, and positive (compassion satisfaction) and negative (burnout and compassion fatigue) domains of professional quality of life. Methods: Using a cross-sectional design, a convenience sample of 221 oncology nurses recruited from several public hospitals filled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
184
5
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(222 citation statements)
references
References 22 publications
13
184
5
20
Order By: Relevance
“…Nurses who experience a high degree of compassion satisfaction in their work perceive a more positive working environment, which contributes to the reduction of burnout. On the contrary, those experiencing a high degree of compassion fatigue perceive a more negative working environment thus experimenting a higher degree of burnout [63]. Moreover, recent research has shown that optimism, hardy personality or emotional competence are factors that protect the individual against burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses who experience a high degree of compassion satisfaction in their work perceive a more positive working environment, which contributes to the reduction of burnout. On the contrary, those experiencing a high degree of compassion fatigue perceive a more negative working environment thus experimenting a higher degree of burnout [63]. Moreover, recent research has shown that optimism, hardy personality or emotional competence are factors that protect the individual against burnout.…”
Section: Discussionmentioning
confidence: 99%
“…This may affect the importance that each culture gives to the factors involved in the onset of the syndrome and their interpretation, limiting the generalization of the results to developing countries. Added to this, despite the similarity of factors that have been related to nurses' burnout by researchers in Europe, the United States [63] or Australia [90], it may occur that the distinct cultural differences, social politics or economic conditions among them may affect the attention given to the specific ones influencing burnout in nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that higher managerial support was associated with higher compassion satisfaction (Hunsaker, Chen, Maughan, & Heaston, ) and that authentic leadership related to compassion satisfaction (Kelly & Todd, ). In addition, a previous study reported that cohesive teamwork environments predicted compassion satisfaction (Wu, Singh‐Carlson, Odell, Reynolds, & Su, ). However, there is no research on the relationship between nursing work environments and compassion satisfaction considered various factors within the environments such as staffing, resources and nurse participation in hospital affairs.…”
Section: Introductionmentioning
confidence: 96%
“…The rates of burnout and compassion fatigue are increasing among healthcare professionals (HCPs) in the US and other developed countries (Banerjee et al, ; Gomez‐Urquiza et al, ; Shanafelt et al, ; Wu, Singh‐Carlson, Odell, Reynolds, & Su, ). Burnout and compassion fatigue directly affect the health of the clinician and research shows that clinician well‐being has a direct impact on patient health outcomes (Salyers et al, ).…”
Section: Introductionmentioning
confidence: 99%